A Forecasting Model for Japan's Unemployment Rate - Takamitsu KURITA (Eurasian Journal of Business and Economics, 2010)
This note aims to achieve a parsimonious fractionally-integrated autoregressive and moving average (ARFIMA) model for recent time series data of Japan's unemployment rate. A brief review of the ARFIMA model is provided, leading to econometric modeling of the data in the ARFIMA framework. It is demonstrated that the preferred ARFIMA model is a satisfactory representation of the data and is useful as a forecasting device.